Features of interpersonal relationships in adolescents with internet addiction - Myloslavska, O.; Huliaieva, O.; Farafonova-Nekrasova, O. (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2023)
The article is focused on the study of interpersonal relations in adolescents with Internet addiction. The purpose of the article is to identify the characteristics of interpersonal relationships and their relationship with Internet addiction in adolescents. To achieve the research goal, the following psychological tools were used: the «Internet Addiction Scale», the «Dialogic Interpersonal Relationships Scale», and the «Diagnosis of emotional barriers in interpersonal communication». The Kolmogorov-Smirnov criterion and Spearman's rank correlation coefficient were used for statistical processing of the results, which allow for further qualitative analysis of the data. According to the results of the study, the relationship between emotional obstacles in interpersonal communication and Internet addiction in Internet addicts and Internet independent adolescents was established. The obtained results indicate that with the growing feeling of inability to overcome the desire to access the Internet; a sense of discomfort if you have to stop using the Internet for a certain period of time, inability to control the duration of time spent for the Internet, the inability to control emotional reactions, the ability to restrain or dose the manifestations of unpleasant emotional experiences, increases internal tension, the tendency to inadequate expression of emotions is actualized; emotional reactions are more often inappropriate. As a conclusion, it can be argued that in the group of adolescents with Internet addictive behavior, with the increase in the severity of emotional barriers in interpersonal communication, a number of Internet addiction symptoms such as "inability to control emotions", "compulsive symptoms", "withdrawal symptoms", "inadequate expression of emotions", "dominance of negative emotions" and "unwillingness to get closer to people on an emotional basis" are exacerbated. The results obtained can be used to improve programmes for the prevention and correction of Internet addiction in adolescents.